Factors predictive of thrombotic events in LUMINA, a multi-ethnic cohort of SLE patients (LXXII) - Burgos, Paula I. (Oxford University Press, 2010)
Objective. Thrombosis is an important cause of morbidity and mortality in SLE. We have explored the factors associated with time to the occurrence of thrombotic events in SLE patients to expand our cohort’s previous observations. Method. SLE patients (ACR criteria), age ≥16 years, disease duration ≤5 years at enrolment (T0), African-American, Hispanic (Texan or Puerto Rican) or Caucasian ethnicity, from LUMINA, a longitudinal cohort, were studied. An event was defined as the presence of arterial or venous thrombosis. Time to the first thrombotic event was examined by univariable and multivariable (MV) Cox models adjusting for pertinent baseline clinical and socio-demographic variables. Results. A total of 643 patients were studied; mean (s.d.) age was 36.4 (12.6) years and disease duration at T0 was 1.4 (1.3) years; 90% were female. After T0, 81 (12.6%) patients had developed a thrombotic event. In the MV model, age [hazard ratio (HR) = 1.06; 95% CI 1.03, 1.08; P < 0.0001], health insurance (HR = 0.53; 95% CI 0.30, 0.94; P = 0.029), smoking (HR = 1.85; 95% CI 1.01, 3.40; P = 0.048), damage (T0) (HR = 1.44; 95% CI 1.20, 1.71; P < 0.0001), aPL (HR = 2.12; 95% CI 1.19, 3.76; P = 0.011) and glucocorticoid (highest dose) (HR = 1.01; 95% CI 1.01, 1.02; P < 0.0001) were significant. Conclusions. Age, poverty, smoking, damage accrual, aPL and higher doses of glucocorticoids were independently associated with a shorter time to the first thrombotic event; health insurance had a protective effect. Acting upon modifiable risk factors at the personal (smoking, high-dose glucocorticoids) and societal (poverty, health insurance) levels may prevent these events and improve the long-term outcome of SLE patients.